Reconstructing Notarial Liability in Sale and Purchase Binding Agreements in Indonesia - Sulaiman; Yusrizal Hasbi; Muhamad Helmi Md Said; Faisal (Sriwijaya Law Review, 2026)
This study examines the professional liability of notaries for drafting Sale and Purchase Binding Agreements (PPJB) in Indonesia, which serve as preliminary contracts when a Sale and Purchase Deed (AJB) cannot yet be executed, but often give rise to legal disputes. Such disputes commonly stem from negligence in verifying the object's legality, weak application of the precautionary principle, and partiality toward one party. Using normative legal research, this study analyses primary, secondary, and tertiary legal materials using descriptive and analytical methods, drawing on statutory, conceptual, and case approaches. The findings show that notaries' professional liability in PPJB transactions rests on five core elements: compliance with positive law, application of the precautionary principle, neutrality, protection of the parties' interests, and observance of professional ethics. Establishing a causal link between notarial acts or omissions and parties' losses requires an integrated evidentiary approach that combines factual and juridical causation, particularly the doctrines of conditio sine qua non and adequate cause. Sanctions must be imposed proportionately, taking into account the degree of fault, the nature of the violation, and its impact, ranging from administrative and ethical sanctions to civil and criminal liability. The novelty of this research lies in formulating an integrative and systematic framework that connects notarial professional standards, causation doctrines, and proportional sanctions within PPJB disputes. This framework clarifies notarial accountability and strengthens preventive legal practice nationwide.